METHODS OF STRATIGRAPHY: POSSIBILITIES & WEAKNESSES. DANGERS & PERSPECTIVES - Ζαμπετάκη-Λέκκα Α.; Κεμερίδου Α. (Bulletin of the Geological Society of Greece, 2006)
Stratigraphy is the science that studies the arrangement of geological formations, as well as the events that influence it, aiming at the reconstruction of earth’s history, which is recorded in two components: time and space. As an empiric science, it studies field data using the knowledge of many scientific fields (petrology, mineralogy, sedimentology, paleontology, physics, tectonics, chemistry, astronomy, statistics, informatics etc) and various analytical methods such as lithostratigraphy that includes sequence stratigraphy, facies stratigraphy and cyclostratigraphy, seismostratigraphy, chemostratigraphy, magnetostratigraphy, biostratigraphy and isotopie chronology. Each one of these methods presents advantages as well as disadvantages, therefore, in order to reach reliable conclusions, the close and continuous collaboration between these methods is considered essential. Particular attention is required through all the stages of the stratigraphie research, from the observation in the field and the collection of data up to their analysis and their interpretation, in order to avoid any influence by the prevailing theories and models of interpretation